Assessing workplace ergonomic towards facilities satisfaction / Muhammad Amiruddin Md.Samsudin - Md.Samsudin, Muhammad Amiruddin (Faculty of Architecture , Planning and Surveying, 2015)
The ergonomic is important thing to consider as they draws on a number of scientific disciplines, including physiology, biomechanics, psychology, anthropometry, industrial hygiene, and kinesiology (OSHA, 2000). Ergonomic is defined as the study of work and specifically is a science of designing the job to fit the worker, rather than physically forcing the worker’s body to fit the job. So, this studies reveal the actual assessment feedback from the different case study selected to shows the right result of the ergonomic problems related to office worker toward their facilities provided that may occur in the problem statements. From the result of this research it will clearly show the workers satisfaction towards their workplace facilities in order to develop better performance of work. In the finding of this study, the different faculty for case study indicate a different result that may concern in the design of the workplace and their types of work related. The end of this research will developed a conclusion of the collected data from the tools and questionnaire that are distributed to the respondents within their workplace in the selected case study.